A systematic review investigating associations between parenting style and child feeding behaviours. Issue 6 (6th January 2014) - Collins, C.; Duncanson, K.; Burrows, T.
Abstract Background A direct association between parenting style and child feeding behaviours has not been established. This review explores whether an authoritative, authoritarian or permissive parenting style is associated with parental pressure to eat, responsibility, monitoring or restriction of child dietary intake. Methods A search of eight electronic health databases was conducted. Inclusion criteria were children aged <12 years, published between 1975 and 2012, measured and reported associations between parenting style and child feeding behaviours. Results Seven studies (n = 1845) were identified in the review. An authoritarian parenting style was associated with pressuring a child to eat and having restrictive parental food behaviours. Authoritative parenting was associated with parental monitoring of child food intake. A permissive parenting style was inversely related to monitoring of child dietary intake. Conclusions Parenting styles showed only weak to moderate associations with individual domains of child feeding. The most consistent relationship found was a negative association between permissive parenting and monitoring for both mothers and fathers in two studies. Progress in this field could be achieved by conducting studies targeting fathers and culturally diverse populations, and development of a tool which could reflect overall child feeding behaviour rather than individual domains.